Problems of Business Education in Junior High Schools (SMP): Systematic Literature Review (SLR) - Moh Nasir Jazuli; Abdul Wahab; Dian Mulyasari; Aniek Indrawati; Ludi Wishnu Wardana (Brilliant International Journal Of Management And Tourism, 2023)
This study aims to determine the problems of implementing business education in social studies as an implementation of entrepreneurship at the junior high school level. This study uses the Systematic Literature Review (SLR) method by collecting and analyzing journals related to keywords. Based on the literature study conducted, it was found that there was still a lack of understanding of junior high school students in the concept of business education in social studies lessons, because the delivery of material was often not accompanied by existing examples and too much material was presented. In addition, students are less motivated to look for reference materials related to the material provided. Based on the analysis of the subject syllabus in social studies, the material taught is too dense but lacks depth and the expected competencies are not clear. In addition, learning activities are still centered on the teacher. The results of the analysis of reference books to see the contents of the material, especially the main economic activity material. How the material is presented, examples, practice questions, and assignments in accordance with the existing subject syllabus. After the basic economic activity reference book is reviewed as teaching material in accordance with the syllabus that has been developed.